Malawi : First Review Under the Three-Year Extended Credit Facility Arrangement and Requests for Modification and Waivers of Nonobservance of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Malawi. (IMF Staff Country Reports; Country Report, 2018)
Malawi's economic growth remains moderate, reflecting a weak agricultural harvest and continued electricity shortages. Fiscal deficits continue to be financed domestically, as donor funding remains constrained by governance concerns since the 2013 cashgate scandal, resulting in an increasing public debt burden. Presidential elections are scheduled for mid-2019. Program performance. Most quantitative performance criteria (QPC) were met at end-June 2018, with significant overperformance on international reserves and the reduction in Reserve Bank of Malawi (RBM) holdings of government securities. The QPC on the primary fiscal balance was missed by 0.9 percent of GDP due to expenditure overruns. The continuous QPC on new non-concessional external debt was missed due to a technical oversight in the Technical Memorandum of Understanding. Based on corrective measures, the authorities request waivers of non-observance. Two structural benchmarks were observed and most of the rest have been completed with delay.